A bipolar electrospray source of singly charged salt clusters of precisely controlled composition. Issue 6 (3rd June 2017) - Fernandez de la Mora, Juan; Barrios-Collado, César
ABSTRACT: The few clusters [B − n A + n+1 ] + ( n = 0, 1) with resolvable mobilities formed in electrosprays of large salts have been used for nanoparticle instrument testing and calibration at sizes smaller than 2 nm. Extensions of this modest size range by charge reduction with uncontrolled gas phase ions has resulted in impure singly charged clusters. Here, we combine two oppositely charged electrosprays of solutions of the same salt B − A +, including: (Cn H2n+1 )4 N + Br − ( n = 4, 7, 12, 16), the large phosphonium cation (C6 H13 )3 (C16 H33 )P + paired with the anions Im − [ (CF3 SO2 )2 N − ] or FAP − [ (C2 F5 )3 PF3 − ], and the asymmetric pair [ 1-methyl-3-pentylimidazolium + FAP − ]. Both polarities are simultaneously produced by this source in comparable abundances, primarily as singly charged A + n B − n ± 1, with tiny contributions from higher charge states. Some but not all of these clusters produce narrow mobility peaks typical of pure ions, even beyond n = 43. Excellent independent stable control of the positive and the negative sprays brought very close to each other is achieved by isolating them electrostatically with a symmetrically interposed metallic screen. Two nanoDMAs covering the size range up to 30 nm (Halfmini and Herrmann DMAs, with classification lengths of 2 and 10 cm) are characterized with these standards, revealing resolving powers considerably higher than previously seen with unipolar electrospray sources. The bipolar source of pure and chemically homogeneous clusters described permits studying size and charge effects in a variety of aerosol instruments in the 1–4 nm size range. Copyright © 2017 American Association for Aerosol Research